Outlooks on neuropsychological rehabilitation of patients with oropharyngeal cancer - G. A. Tkachenko; E. I. Skvortsova (Опухоли головы и шеи, 2019)
This article discusses the problem of cognitive function deterioration in patients with oropharyngeal cancer after treatment. We describe the main factors impeding objective evaluation of cognitive functions in these patients, etiologic factors of cognitive disorders, and the impact on the quality of life.